Scientific and Technological Ties Optimization Considering Companies’ Innovative Development Programmes Implementation with Public Ownership - V. L. Abramov; S. I. Bortalevich; Y. L. Loginov (Управленческие науки, 2016)
The article considers the arrangement of complex events oriented to companies’ scientific and technological ties optimization with public ownership and other organized (innovative) agents united by integrated scientific and technological cycles. On the basis of analytical models usage it is suggested the qualitative raising of Russian companies observability playing a key role in the formation, implementation and utilization of the basic innovations block, new scientific and manufacturing technologies worked out on their basis. For insuring Russian companies’ scientific and technological ties optimization playing a key role in the formation, implementation and utilization of the basic innovations block, new scientific and manufacturing technologies worked out on their basis within the forecast configurations of the future’s technological modes the constructing of the new management system is required. It is particularly important concerning the companies with public ownership and technologically cooperated with them the organizations of all ownership forms within the group of the basic innovations with heterogeneous participants as the aggregate of organizational (innovational) agents (legal entities, creative teams, network communities, etc.). The system result is the access to dynamic analysis of the heterogeneous participants’ activity in the operational area of the Russia National innovative system with the account of structure and address configuration of co operational scientific and technological ties between innovational agents within the Eurasian Economic Union for their optimization.